Treatment of a buccosinusal fistula using buccal adipose tissue: a case report (Research, Society and Development, 2022)
The objective of this paper is to present a case report of a bucco-sinusal fistula with surgical approach using buccal adipose tissue. Male patient, 27 years old, attended the Hospital da Restauração Governador Paulo Guerra, Recife-PE, with a symptomatic complaint in the alveolus region of tooth 16 post-exodontia 4 months ago, as well as passage of liquid from the oral cavity to the nasal cavity, bad breath and sinusopathy. The intraoral examination revealed a defect in the alveolar ridge compatible with fistula in the region of the alveolar ridge of tooth 16. A face CT scan showed a hypodense region compatible with bone fenestration in the maxillary alveolus of approximately 04 cm, closing the diagnostic hypothesis of a bucco-sinusal fistula. Antibiotic therapy and nasal decongestant were started 5 days before surgery. The patient underwent general anesthesia, an incision on the alveolar ridge contouring the fistula associated with an anterior relaxing incision, tissue displacement and divulsion until exposure of the buccal fat body extension, which was used as a pedicled graft to close the fistula. The patient is being followed up for 3 months with no sign of recurrence. In light of the above, we conclude that the use of Bichat's ball is a safe and effective method in cases of reconstruction of small to medium-sized fistula buccosinusal defects.